THE LAW ENFORCEMENT IN OVERCOMING UNDERAGE PROSTITUTION CRIME - Erniyanti, Erniyanti (UNISSULA, 2023)
The purpose of this research is to analyzing legal enforcement in calculating the crime of prostitution under age, A child is very vulnerable to influence, various kinds of tricks the perpetrators try to trick their victims, with tantalizing false promises, so that the victim is hypnotized to follow the lust and evil plans of the perpetrators. Victims of child prostitution can be without or with the use of force, violence or deception because children are unable to give consent to exploit themselves. This research uses a normative juridical research approach. There are several important roles in overcodming or tackling child prostitution activities, namely from several government agencies, schools and families. We recommend that law enforcers in Indonesia be more assertive in tackling the occurrence of criminal acts of prostitution in children, the role of society and families is also needed in addressing the existence of prostitution in children by paying attention to their children and providing knowledge or insight into increasing religion in children.